PRODUCTION COSTS MAPPING TO SUPPORT THE CANVAS MODEL BUSINESS (BMC) AT BUMDES PULOTONDO MULYO - TULUNGAGUNG - Fatimah, Annisa; Sari, Novita Permata; Syarifah, Saila Izza (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this applied research is to map production costs to support business feasibility analysis using the Business Model Canvas (BMC) method for Pulotondo Mulyo Village-Owned Enterprises, called BUMDes, which have a variety of potential superior products. Observations were made on business activities, interviews and documentation to collect data. The BMC method is used to design, outline and develop a company's business model which consists of nine key elements that cover all important aspects of a business, starting from the value proposition offered to customers, the resources needed to produce that value, to the way the company interact with customers and earn revenue. For this reason, as support for one of the elements required in BMC, this research calculates the cost of production using the full costing method to determine the appropriate selling price for BUMDes' superior products, namely Catering and Maggot (from Black Soldier Fly – BSF) products using the cost based pricing method in order to be able to compete with competitors and covers a wide market share. After these stages, a business feasibility analysis is carried out using Payback Period (PP), Net Present Value (NPV), and Internal Rate of Return (IRR). The research results stated that the business was declared worthy of development.